Caffeine Metabolism and its Effects on Brain Biochemistry - Ma'mura, Valijonova (American Journal of Biomedicine and Pharmacy, 2026)
Caffeine (1,3,7-trimethylxanthine) holds the distinction of being the most broadly consumed neuroactive substance in recorded human history, with habitual intake documented across diverse geographic, cultural, and socioeconomic populations. Despite its familiarity, the molecular pharmacology underlying its central nervous system effects involves a constellation of biochemical events that extend considerably beyond simple neuronal stimulation. This narrative review synthesizes peer-reviewed evidence published between 2021 and 2026 to address four principal questions: (i) how hepatic cytochrome P450 1A2 (CYP1A2) mediates N-demethylation of caffeine into its pharmacologically active primary metabolites—paraxanthine, theobromine, and theophylline; (ii) through what structural and kinetic mechanisms caffeine competitively antagonizes adenosine A1 and A2A receptors; (iii) how that receptor-level antagonism propagates into altered dopaminergic, glutamatergic, GABAergic, and noradrenergic neurotransmission; and (iv) what the long-term neurobiological consequences of habitual intake are, including modulation of neuroplasticity and potential protective effects against Alzheimer's and Parkinson's diseases. Collectively, the evidence positions caffeine as a dose-sensitive neuromodulator whose biochemical footprint in the brain is substantially more complex than its widespread, culturally normalized status might suggest.